A Case Study of Household Food-Related Assessment Using an Innovative Passive Dietary Assessment Device in Mampong-Akuapem, Ghana (FS17-03-19). (13th June 2019) - Anderson, Alex; McCrory, Megan; Steiner-Asiedu, Matilda; Ansong, Richard; Lewis, Clara; Ghosh, Tonmoy; Higgins, Janine; Sazonov, Edward
Abstract: Objectives: Traditional dietary assessment methods in low-middle income countries (LMICs) have significant limitations. The objective of this study was to test the feasibility of using the Automatic Ingestion Monitor (AIM), an eyeglasses-mounted wearable chewing sensor and micro-camera, to monitor food acquisition, preparation and consumption of a household in a LMIC setting. Methods: This is a case of an 8-member household from Mampong-Akuapem, a semi-rural community in the Eastern Region of Ghana. The household was made up of mother (35 years), father (37 years), and six children (ages 17 years, 13 years [twins], 8 years, 5 years, and 18 months). Mother has no formal education and works as a cook, whereas the father has elementary education and is a farmer/construction worker. All members of the household consume the same prepared meals. The AIM was used to monitor household activities for a day. The primary food preparer (mother) wore the AIM during all waking hours on the chosen day as she went about her daily activities, except any activities where she wanted to preserve privacy. The mother also responded to a socio-demographic questionnaire and evaluated her perceived burden of wearing the AIM. Images captured by the AIM were processed and annotated in custom software. Major household related activities around food are reported. Results: Overall, a total wear time of 776 minutes (12.9 hr; 76.1% of usual wake time) was recorded with images spanning a total of 681 minutes (11.4 hr; 87.8% of total wear time). Cooking and food preparation (four different meals) accounted for 47.9%, shopping 1.5%, breastfeeding and other child feeding 5.1%, and eating 5.4% (communal 4.9% and non-communal 0.5%), and other daily activities 40.1% of usual wake time. Three main meals captured on the AIM were breakfast (rice porridge - boiled watery rice with added sugar, milk and bread), lunch (fufu - pounded boiled cassava and plantain, and chicken soup), and dinner (kelewele - fried spiced yellow plantains). The AIM was generally accepted by the participant and household members although they preferred a smaller size version. Conclusions: The AIM has the potential of capturing household food related activities and practices that affect dietary intake and nutritional health in LMIC. Funding Sources: Funded by the Bill & Melinda Gates Foundation.